Halal Lifestyle and Consumer Decisions: The Role of Halal Labels, Religious Values, and Word of Mouth in Purchasing Wardah Cosmetics at Islamic Boarding Schools - Wahab, Wahab; Wijayanti, Ratna; Kristiyani, Dwi; Prawoto, Eko (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2023)
The domestic cosmetic industry in Indonesia continues to experience steady growth, driven by increasing market demand and evolving beauty trends. This demand is fueled by consumer interest in multifunctional cosmetic products. This study examines the influence of product attributes, halal labels, religiosity, and word of mouth (WOM) on purchasing decisions for Wardah cosmetics among female students at an Islamic boarding school in Kalibeber, Mojotengah, Wonosobo. Using a quantitative approach and linear regression analysis, data were collected from 100 respondents selected through random sampling. The results indicate that all four factors significantly impact purchasing decisions. Product attributes positively affect consumer choices, highlighting the importance of quality, design, and features. Halal labels play a crucial role in building trust and ensuring compliance with Islamic principles. Religiosity strongly influences decision-making, as students prioritize products aligned with their faith. WOM also significantly impacts purchasing behavior, especially within close-knit communities. Collectively, these variables explain 50% of the variance in purchasing decisions. The findings emphasize the need for manufacturers to focus on product development, clear halal certification, and strategies that encourage positive WOM to enhance consumer trust and brand loyalty in religiously conscious markets.